In vitro antibacterial and antibiofilm activities of isobavachalcone against Enterococcus faecalis clinical isolates from China - Lili Ouyang; Zhicao Xu; Yuanyuan Tang; Duoyun Li; Zhijian Yu; Zewen Wen; Haigang Zhang; Chaoqin Zhang (BMC Microbiology)
Abstract Background The pharmacological activities of the natural product isobavachalcone, such as antimicrobial activity, reverse transcriptase blockade, and antioxidant property have been extensively reported. Whereas, its antimicrobial and biofilm-inhibitory effects on clinical E. faecalis strains in China, along with its potential mechanisms, are still not fully clear. This research is intended to assess the in vitro antibacterial and anti-biofilm effects of isobavachalcone against clinical E. faecalis isolates sourced from China. Moreover, it further explores the potential target site of it within E. faecalis. Results It was found that the minimum inhibitory concentrations (MICs) of isobavachalcone ranged from 6.25 to 12.5 µM against 220 E. faecalis clinical strains obtained from a tertiary hospital in China. The antibiofilm activity of it with sub-MIC concentration ( 1/2 × MIC ) against the biofilm formation of E. faecalis was demonstrated and Time -killing curve assay revealed the quick bactericidal effect of isobavachalcone against E. faecalis planktonic cells. However, no synergetic bactericidal activity of isobavachalcone co-administered with vancomycin, or ampicillin was observed for eradicating the biofilm. Moreover, isobavachalcone-resistant E. faecalis was isolated by in vitro induction of isobavachalcone, and whole genome sequencing was performed to determine the genetic mutations of ten functional proteins in isobavachalcone-resistant E. faecalis, including PurH and FlgJ, with the other eight proteins being related to cell wall or cell membrane biogenesis, DNA synthesis, and energy metabolism. In addition, molecular docking results indicate that there is a potential binding of isobavachalcone and PurH protein in E. faecalis. Conclusion This research highlights the potential of isobavachalcone as a potent antibacterial agent against E. faecalis clinical isolates, capable of significantly inhibiting biofilm formation at sub-MIC concentrations. PurH protein in E. faecalis might serve as a potential target of isobavachalcone and the specific action mechanism of isobavachalcone needs further study.